Literacies in school and the student’s formation as a historical subject in times of Saeb (Olhar de Professor, 2024)
The present study analyzes the literacy events proposed for the lessons of the Portuguese language subject in two classes in the 3rd grade of high school at a state school of Anápolis-GO. The research is qualitative and was held between the months of August and November 2021, upon the return to in-person classes due to the Pandemic. The interpretation of the data is based on literacy studies (Rojo, 2009; Soares, 2009; Street, 2014), understanding its importance in the students’ shaping as historical subjects, who are more aware of their place in the world and their ability of modifying their context. We observed a teaching that aimed at obtaining results in the Saeb, so that the teaching practices carried out in the classes, during the months of study, were based on the conception of autonomous literacy (Street, 2014), which is characterized by being disconnected from the students’ context and contribute to the formation of passive subjects.
Keywords: Portuguese language; Social literacies; Literacy events; Subject-agent